Strategi Pengelolaan PPN dalam Meningkatkan Profitabilitas Bisnis - Indy, Listia Aulia; Lamsah, Lamsah (Universitas Pahlawan Tuanku Tambusai, 2025)
Value Added Tax (PPn) is one of the important components in the Indonesian tax system that directly affects a company's cash flow and profitability. An effective PPn management strategy can be an instrument to maximize tax efficiency, minimize compliance risks, and increase overall business profitability. This Community Service Activity aims to examine various PPn management strategies that can be applied by business actors including students who are starting to become entrepreneurs, and analyze their impact on business profitability. The method used is direct observation then identifying problems followed by counseling and socialization ending with evaluation. The results of this community service activity show that students are able to understand that strategies such as optimizing input and output tax administration, utilizing PPn restitution in a timely manner, and digitizing tax reporting contribute significantly to increasing efficiency and profit margins.